ZAMANAGÓY JOQARÍ BILIMLENDIRIW PROCESINDE RUWXÍY-ÁDEP-IKRAMLÍLÍQ TÁRBIYANÍŃ ORNÍ HÁM ROLI - Muratbaeva, A.J. (SCIENCE and SOCIETY, 2025)
The article reveals the essence, content, purpose, and main aspects of spiritual and moral education. The role and significance of spiritual and moral education in the process of higher education, the main directions and methods of moral education of student youth are analyzed. The work is based on the analysis of regulatory legal documents and research by contemporary scholars.